Shared watercourses and water security in South Asia : challenges of negotiating and enforcing treaties - Salman, Salman M. A., 1948-; Uprety, Kishor, 1958- (Leiden ; Boston : Brill, 2018)
The monograph discusses the various challenges facing shared water resources in South Asia, and the response of most these countries, presented in their calls for water security. Consequently, negotiating new transboundary water treaties amongst South Asia's riparian countries has become a daunting task, and enforcing existing ones remains a real challenge.
Includes bibliographical references.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Water security -- South Asia; Water resources development -- South Asia; Water-supply -- Political aspects -- South Asia; Water-supply -- South Asia -- International cooperation; International rivers -- South Asia; elektronické knihy; electronic books